PENGENDALIAN PENGELOLAAN OBAT DI INSTALASI FARMASI SUATU RUMAH SAKIT SWASTA KOTA BANDUNG - Lisni, Ida; Samosir, Herman; Mandalas, Ester (Jurnal Riset Kefarmasian Indonesia, 2021)
Drug management is a series of planning, procurement, storage, distribution, and control activities carried out by a hospital pharmacy so that drug availability can be guaranteed in sufficient quantities, in its implementation requires a large number of funds. The study was conducted to evaluate drug management in private hospital pharmacies in the city of Bandung using predetermined standard indicators. This study used a retrospective non-experimental observational method. The data collected is in the form of planning data and drug procurement, drug use, drug stock cards, stock-taking reports. The results showed that the achievement of drug planning (107.53%), the frequency of purchase for the low category (34.70%), the medium category was 41.08% and the high category (24.22%), expired drugs (0.085%) and the dead stock (3.81%).